Trust me if you can: The effect of driver username on passengers' intention to use ride‐sharing service. Issue 2 (3rd July 2022) - Fu, Huijian; He, Junhong; Hong, Jianhong; Hu, Linfeng
Abstract: Building trust and enhancing consumers' participation are critical for the growth of peer‐to‐peer sharing economy. This research explores the effect of driver username on passengers' intention to use ride‐sharing service and its underlying psychological mechanisms. The results indicate that driver username has a significant impact on passengers' intention to use ride‐sharing service, as a driver with a real name elicits greater intention to use ride‐sharing service than a driver with a screen name (studies 1, 2, 3a, 3b, and 3c). In addition, the effect of driver username on passengers' intention to use ride‐sharing service is serially mediated by social presence and trust (study 2). Importantly, the effect of driver username on passengers' intention to use ride‐sharing service is moderated by driver reputation (studies 3a, 3b, and 3c). A high (vs. low) reputation facilitates the impact of driver username on passengers' usage intention. Based upon these findings, theoretical and practical implications are discussed.